Spatial analysis of the distribution of banks and commercial banks in the city of Hail, a study using geographic information systems (GIS) - Alshamri, Maryam Radhi Sayah (Journal of Humanities & Social Sciences, 2025)
This study aimed to reveal the pattern of spatial distribution of banking buildings in the city of Hail, and it is a study using geographic information systems. The study dealt with the reality of the distribution of banks and commercial banks in the city of Hail. And commercial banks, as well as the historical approach in identifying the spatial development of banks and commercial banks in the city of Hail, and the study used some statistical methods and methods that were applied to analyze the data and draw conclusions from them. During which the coordinates of the geographical locations of the bank buildings were recorded, and the study relied on methods, the spatial average, the standard distance, the direction of distribution, and the central phenomenon. It had an effect on the distribution of banks and commercial banks in the city of Hail, the concentration of most banks and commercial banks in the center of the city of Hail, specifically in the airport neighborhood and the Subarea neighborhood, the study concluded that there is a central phenomenon of banks and commercial banks within the city of Hail in the Barzun district, and that the standard distance analysis came on the distribution The 41 neighborhoods, to represent the direction of distribution of most of the vocabulary of the phenomenon of banks and commercial banks in the city of Hail, which includes a group of 43 neighborhoods. The study showed that the northern and southern neighborhoods of Hail lack some banks and commercial banks.
Keywords: Banks and banking; Hail city; Saudi Arabia; Banking services; Economic geography; Urban planning